PERBANDINGAN BUKU MATEMATIKA UNTUK SD/MI 5B DAN SENANG BELAJAR MATEMATIKA BERDASARKAN KESESUAIAN KARAKTERISTIK PMRI - Siti Rohmah Tuwloh Hulumah, - (2021)
Abstrak: Buku teks merupakan buku yang berisi uraian bahan ajar pelajaran tertentu yang tersusun secara sistematis dan terseleksi berdasarkan tujuan tertentu, orientasi pembelajaran dan perkembangan siswa. Penelitian ini di latar belakangi oleh penggunaan buku matematika kelas V yang berjudul Matematika untuk SD/MI 5B di salah satu SD di Kabupaten Sukabumi. Sementara buku yang diterbitkan oleh kemendikbud berjudul Senang Belajar Matematika. Penelitian ini bertujuan untuk mendiskripsikan kesesuaian buku yang berjudul Matematika untuk SD/MI 5B dan buku Senang Belajar Matematika berdasarkan karakteristik pendidikan matematika realistik indonesia, serta perbedaan dari ke dua buku tersebut. Teori tentang karakteristik PMRI yaitu The use of context, The use of model, The use of student's own productions and contructions, The interactive character of teaching process dan The interwinement of various learning strands digunakan untuk menganalisis kesesuaian kedua buku dan perbedaan kedua buku. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan desain penelitian deskriptif komparatif. Penelitin ini dipaparkan berdasarkan hasil studi dokumentasi, wawancara dan angket terbuka. Berdasarkan hasil penelitian, persentase kesesuaian buku Matematika untuk SD/MI 5B dengan karakteristik PMRI sebesar 69. 39%, dan kesesuaian buku Senang Belajar Matematika dengan PMRI sebesar 91, 9%. Buku buku Matematika untuk SD/MI 5B memenuhi 3 karateristik PMRI yaitu The use of context, The use of model dan The interwinement of various learning strands. Sementara buku Senang Belajar Matematika memenuhi 5 karakteristik PMRI yaitu The use of context, The use of model, The use of student's own productions and contructions, The interactive character of teaching process, dan The interwinement of various learning strands. Kata Kunci: Perbandingan Buku Matematika SD Kelas V, Matematika, Karakteristik PMRI Abstract: Textbooks are books that contain descriptions of teaching materials for certain subjects that are systematically arranged and selected based on certain goals, learning orientation and student development. This research was motivated by the use of a fifth grade math book entitled Matematika untuk SD/MI 5B in an elementary school in Sukabumi Regency. Meanwhile, the book published by the Ministry of Education and Culture is entitled Senang Belajar Matematika. This study aims to describe the suitability of the book entitled Matematika untuk SD/MI 5B and the Senang Belajar Matematika based on the characteristics of Indonesian realistic mathematics education, as well as the differences between the two books. The theory of PMRI characteristics, namely The use of context, The use of model, The use of student's own productions and constructions, The interactive character of teaching process and The interwinement of various learning strands are used to analyze the suitability of the two books and the differences between the two books. The method used in this study is a qualitative method with a comparative descriptive research design. This research is presented based on the results of the study of documentation, interviews and open questionnaires. Based on the results of the study, the percentage of conformity of Matematika untuk SD/MI 5B characteristics was 69. 39%, and the suitability of Senang Belajar Matematika books with PMRI was 91, 9%. Matematik untuk SD/MI 5B book fulfills 3 PMRI characteristics, namely The use of context, The use of model and The interwinement of various learning strands. While the book Senang Belajar Matematika fulfills 5 PMRI characteristics, namely The use of context, The use of model, The use of student's own productions and constructions, The interactive character of teaching process, and The interwinement of various learning strands. Keywords: Comparison of Elementary Mathematics Books for Grade V, Mathematics, PMRI Characteristics